Examining the Role of Technostress Creators and Inhibitors on Academics Burnout - Kamarul Faizal Hashim; Felix B. Tan; Ammar Rashid; Shafiz A. Mohd Yusof (Emerging Science Journal, 2024)
Recent studies have focused on examining the impact of technostress (TS) on academics and students. However, there remains a paucity of studies examining the influence of TS on burnout among academics. This study aims to explore the influence of TS on academics' feelings of burnout and to examine the mitigating role of TS inhibitors on burnout among academics when using online learning technology. A web-based survey was designed and used to collect data from 115 academics in Malaysian universities. The data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The research findings reveal that academic burnout is significantly influenced by technology insecurity, technology invasion, and technology uncertainty. However, the impact of technology overload is only partially significant, while technology complexity does not exert a significant influence on academic burnout. Moderation tests reveal that literacy and involvement facilitation significantly moderate the relationship between technology uncertainty and insecurity, reducing burnout feelings. This study extends existing literature by providing empirical evidence to explain the relationship between TS and the academic burnout construct. Furthermore, it demonstrates the mitigating role of TS inhibitors on the burnout construct. Additionally, it offers potential strategies for alleviating burnout among academics, particularly in Malaysian university contexts. Doi: 10.28991/ESJ-2024-SIED1-012 Full Text: PDF